Analisis Pengaruh Pendampingan, Media Sosial, Dan Inovasi Produk Terhadap Kinerja Usaha Mikro di Kota Depok - Enuh, Kamaludin; Nuraini, Ani; Anwar, Kasful (Melati Institute, 2023)
Micro Enterprises are business activities that are able to expand employment opportunities, provide economic services to the community, play a role in the process of Equalization and increase community income, encourage economic growth, and play a role in realizing national stability.The purpose of this study was to determine the mentoring, social media and product innovation on the performance of micro enterprises in the city of Depok. The method used in this study is a quantitative method. The population of this study was 2,746 and sampling was carried out by cluster sampling as many as 96. Data collection using Google form questionnaires and data analysis techniques used are multiple linear regression test. The results showed that partially mentoring, social media and product innovation on the performance of micro enterprises. Simultaneously mentoring, social media and product innovation on the performance of micro enterprises. The value of R2 is 0.547. This means that the influence of mentoring, social media and product innovation on the performance of micro enterprises amounted to 0.547 or 54.7% while the remaining 45.3% variance in the performance of micro enterprises influenced by other factors not examined in this study.